Leveraging Vaccines to Reduce Antibiotic Use and Prevent Antimicrobial Resistance: A World Health Organization Action Framework. (25th January 2021) - Vekemans, Johan; Hasso-Agopsowicz, Mateusz; Kang, Gagandeep; Hausdorff, William P; Fiore, Anthony; Tayler, Elizabeth; Klemm, Elizabeth J; Laxminarayan, Ramanan; Srikantiah, Padmini; Friede, Martin; Lipsitch, Marc
Abstract : This Action Framework identifies priority actions to prevent antimicrobial-resistant (AMR) through expanding the use of licensed vaccines, developing new vaccines that contribute to the prevention and control of AMR, and expanding knowledge about the impact of vaccines on AMR.